Factors that affect intention to use mobile learning in Yemeni public universities / Ibrahim Mohamed Mohamed Alrajawy - Mohamed Alrajawy, Ibrahim Mohamed (Institute of Graduate Studies, UiTM, 2018)
Despite an enormous number of researches of the mobile learning in developed nations, there are a few researches in the Arab world especially the Republic of Yemen. Furthermore, the recent statistics have shown high-level mobile phone and Internet penetration but the concept of deploy mobile phones in the institutions of higher education in the Republic of Yemen still infant. The objective of this study is to identify the factors that influence the intention to use mobile learning based on the Technology Acceptance Model (TAM). TAM is extended to include three factors (subjective norms, self-efficacy and organizational supports). The research framework consists of six variables (three independents, two mediating and one dependent). Using self-administered survey, 33 items with 7-point Likert scale is used to collect data. Out of the 400 samples, 343 responses (85.75 % response rate) were collected; eventually, 320 responses were usable. Structural Equation Modeling is applied to analyze the data. The findings of this study revealed that subjective norms have a direct effect on both perceived usefulness and perceived ease of use. While self-efficacy and organization support significantly affect perceived ease of use…